Cloud Computing Characteristics and Security Issues - Ayyub, Shaheen; Roy, Devshree (International Journal of Computer Sciences and Engineering, 2013)
Along with the development and application of Cloud Computing in recent years, Cloud Storage, as the module which provides data storage service in the Cloud Computing architecture, has become the kernel component of Cloud Computing. This is one of the advantages of cloud computing to create and store data at remote servers. But this advantage implicitly contains drawback of data security and privacy vulnerabilities. Many algorithms and methodologies are there by which data security in cloud computing can be achieved but at the same time it possesses many security risks. In this paper we describe several aspect of data security.